The Effect of Leverage, Size, Liquidity, Operating Cash Flow on Fixed Asset Revaluation - Dian Firmansyah; Nurmala Ahmar; JMV Mulyadi (STIE Perbanas Surabaya, 2017)
This study tries to prove empirically the effect of leverage, size, liquidity and operating cash flows on the revaluation of fixed assets. It used a sample of all non-financial companies, which revalued assets in the periode of 2012-2015, at companies listed on Indonesia Stock Exchange with upward revaluation category. The analysis was done using Path analysis (PLS) without requiring classical assumption and normality test. The results show that leverage affects Asset revaluation, it proves that high leverage because the company to do revaluation of fixed assets, large companies tend to want to display earnings reports that are not too large to reduce their political costs, with asset revaluation, the value of depreciation is calculated Repeated and reduce the company's profit. Operating cash flows affect the revaluation of fixed assets on the grounds that the company requires funds to pay its obligations as well as in revaluation assets cost a great deal for the appraisal services, audit fees and final tax payments. Yet, liquidity has no effect on the revaluation of fixed assets, Within the last 4 years, the study found that users of the Asset revaluation model reporting in Other Comprehensive Income continue to grow and are expected to become financial statements that have superiority and good quality by reporting fair value. In the next research to add the number of variables on Asset revaluation, as well as expand the sample by involving the company revaluation and non revaluation. In addition, to examine the development of asset revaluation, especially in ASEAN countries related to the adoption of IFRS in the case of fixed asset revaluation.Keyword: Leverage, Size, Liquidity, Cash Flow from operation, and Revaluations Assets.